PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE BERBANTUAN MEDIA 3D PRINTING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI SMA NEGERI 7 LUWU - Sap Sofyan, Asmar; Al Anshori, Fitrah; Syam, Sukmawati; Muhajirah Yunus, Nur (Jurnal Biogenerasi, 2026)
The lack of varied learning models and media has an impact on students' interest, understanding, enthusiasm, and activeness, resulting in low critical thinking skills. This study aims to determine the effect of the Example Non Example learning model assisted by 3D Printing media on the critical thinking skills of class XI students of SMA Negeri 7 Luwu. The type of research used is a quasi-experimental and the design form is a non-equivalent control group design. The sample used in this study were students of class XI MIPA.2 as the experimental class and XI MIPA.3 as the control class. The sampling technique used is purposive sampling. The instrument used in the study was a critical thinking ability test. Data were analyzed using descriptive statistical analysis and inferential statistical analysis. The results of the descriptive statistical analysis test obtained pretest results of 38,7% in the low category and 61,3% in the medium category. While the posttest results obtained 90,3% in the medium category and 9,7% in the high category. The results of the inferential analysis using the t-test obtained a Sig value (2-tailed) of 0,001<0,05. Based on the analysis results, it can be concluded that the implementation of the Example Non-Example learning model assisted by 3D Printing media has an effect on the critical thinking skills of 11th-grade students at SMA Negeri 7 Luwu.